Luteolin Inhibits Listeriolysin O Translation by Directly Targeting the Coding Region of the hly mRNA - Wang, Jianfeng; Liu, Shui; Liu, Bowen; Niu, Xiaodi; Deng, Xuming (Frontiers in Microbiology, 2019)
Listeriolysin O (LLO) is necessary for bacterial escape from the phagosome into the cytoplasm, which suggests that targeting LLO may be an alternative strategy to combat Listeria monocytogenes-mediated infection. Here, luteolin, a natural compound without anti-bacterial activity, as indentified as effective inhibitor of LLO by translationally inhibiting the production of LLO. Additionally, luteolin-treated L. monocytogenes displayed reductions in cytoplasmic growth, cytotoxicity and phagosome escape within macrophages. Molecular modeling and mutational analysis revealed a direct interaction between luteolin and the 5′ coding region (A818, U819, G820, and U830 located in nt 814–849) of the mRNA of hly, the gene encoding LLO, which interfered with its translation. Together, our data demonstrate that luteolin may be used as a novel therapeutic and lead compound for treating L. monocytogenes infection.